Perubahan Prilaku, Pola Komunikasi, dan Hubungan sosial, Anak Akibat Kecanduan Handpone di Lingkungan Keluarga, Sekolah dan Teman Sebaya - Meriyanto Meriyanto; Eka Putra (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid development of digital technology has had a significant impact on children's social lives, particularly through the increasingly widespread use of smartphones at an early age. The phenomenon of smartphone addiction in children has become a complex social and psychological issue because it affects their behavior, communication patterns, and social relationships within the family, school, and peer environment. This study aims to systematically examine the effect of smartphone addiction on changes in children's behavior, communication, and social relationships using a Systematic Literature Review (SLR) approach. The review process was conducted based on the PRISMA protocol on scientific literature published between 2019 and 2025, encompassing 27 selected articles from various academic databases. The analysis results indicate that smartphone addiction impacts increased impulsive behavior, decreased face-to-face interactions, impaired family communication, and reduced empathy and social engagement in children. Key risk factors include weak parental control, social pressure from peers, and unmet emotional needs. Conversely, family support and digital literacy have been shown to act as protective factors. This research contributes to broadening the theoretical understanding of non-substance addictive behaviors in children and provides a basis for developing family-based and educational intervention strategies to establish a healthy balance in digital technology use among children.